Herpetofauna del Parque Sierra de Nanchititla, estado de México, México. Lista, distribución y conservación - Gustavo Casas-Andreu; Xóchitl Aguilar-Miguel (Ciencia Ergo Sum)
The Sierra de Nanchititla Natural Park is located in the southwestern corner of the state of Mexico. Most of the park is contained in the western half of the municipality of Tejupilco, bordered on the west by the states of Michoacan and Guerrero. Physiographically it is located in the Province of Sierra Madre del Sur, in the Subprovince of Depresión del rio Balsas, and represents a transition zone of climate, flora and fauna. A total of 48 species were registered in the Nanchititla Park, including 20 amphibians and 28 reptiles, of which 21 (44%) are new records for the locality